Young Lady with Acute Upper Limb Ischemia due to Cervical Band (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Introduction: Acute upper limb ischemia is usually caused by compression of cervical rib on subclavian artery. But in very few cases compression may be caused by cervical band which is not evident in conventional radiography.Results and Discussion: This is a case of a 26 year old lady, housewife, having rudimentary cervical rib, presented with acute left upper limb ischemia due to subclavian artery aneurysm. Peroperatively cervical fibrotic bandwas identified and diagnosed as the cause of subclavian artery aneurysm instead of rudimentary cervical rib. Scalenectomy, excision of the cervical band, excision of the aneurysmsac and arterial reconstruction of the subclavian artery was performed. Her operation was uneventful, postoperative recovery was excellent. She was discharged to home on 4th postoperative day ensuring good distal pulsation of affected limb.Conclusion: Though rare, cervical band is a cause of acute upper limb ischemia. So, we must not forget while diagnosing this type of cases.J Bangladesh Coll Phys Surg 2015; 33(2): 101-104